2020
DOI: 10.3390/toxins12080488
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Aflatoxin B1, T-2 Toxin, Ochratoxin A and Deoxynivalenol in Dried Seafood Products by LC-MS/MS

Abstract: Mycotoxins are secondary metabolites produced by fungi. These contaminate dried seafoods during processing and storage and represent a potential health hazard for consumers. A sensitive, selective and accurate liquid chromatography/tandem mass spectrometry (LC-MS/MS) method was established for simultaneous quantification of four common mycotoxins (aflatoxin B1 (AFB1), T-2 toxin (T-2), ochratoxin A (OTA) and deoxynivalenol (DON)) in dried shrimp, dried fish and dried mussel products. Mycotoxins were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…Contrary to our results, Deng et al [40] observed the presence of AFB1, T-2, and OTA at levels of 0.58-0.89, 0.55-1.34, and 0.36-1.51 µg/kg, respectively, in dried seafood after ultrasound treatment for 60 min at 20 • C. However, these authors employed an acetonitrile/water mixture (85/15, v/v) as an extraction solvent. It is important to point out the importance of the solvent employed in mycotoxins recovery.…”
Section: Mycotoxin Presence In Sea Bass Side Streamscontrasting
confidence: 99%
“…Contrary to our results, Deng et al [40] observed the presence of AFB1, T-2, and OTA at levels of 0.58-0.89, 0.55-1.34, and 0.36-1.51 µg/kg, respectively, in dried seafood after ultrasound treatment for 60 min at 20 • C. However, these authors employed an acetonitrile/water mixture (85/15, v/v) as an extraction solvent. It is important to point out the importance of the solvent employed in mycotoxins recovery.…”
Section: Mycotoxin Presence In Sea Bass Side Streamscontrasting
confidence: 99%
“…Furthermore, Deng et al. (2020) reported LOD and LOQ ranging 0.1 to 2.0 and 0.3 to 5.0 µg/kg, respectively, using a LC‐MS/MS for the detection of mycotoxins including aflatoxins in dried seafood samples.…”
Section: Current Aflatoxin Detection Methodsmentioning
confidence: 99%
“…The necessity to monitor mycotoxins also in dried seafood products has recently led to the development of a sensitive, selective and accurate LC-MS/MS for the quantification of aflatoxin B1, T-2 toxin, ochratoxin A and deoxynivalenol in these specific matrices [ 69 ]. After comparing different sample preparation approaches, the optimized method was based on an ultrasound-assisted acetonitrile/water extraction followed by a defatting clean-up with n-hexane.…”
Section: Mycotoxinsmentioning
confidence: 99%